Clopidogrel non-responsiveness and risk of cardiovascular morbidity - Sofi, Francesco; Marcucci, Rossella; Gori, Anna Maria; Giusti, Betti; Abbate, Rosanna; Gensini, Gian Franco (Thrombosis and Haemostasis, 2010)
We performed this meta-analysis to update the clinical evidences on the relation between clopidogrel non-responsiveness and clinical outcomes in patients with coronary artery disease (CAD) who underwent percutaneous coronary intervention. An electronic literature search through MEDLINE, EMBASE, Web of Science, and the Cochrane Library and bibliographies of retrieved articles up to January, 2009 was conducted. Studies were included if they had a cohort prospective design, if they analysed clopidogrel responsiveness in CAD patients in relation to death and/or occurrence of adverse coronary events during follow-up, and if they reported an adequate statistical analysis. Fourteen studies, totalling 4,564 CAD patients followed for a time ranging from 14 days to one year, were included. The cumulative analysis reported that residual platelet reactivity despite clopidogrel treatment was significantly associated with an increased risk of death and/or thrombotic recurrences (odds ratio [OR] 5.67, 95% confidence interval [CI] 2.97 to 10.84; p<0.00001). However, four studies contributed to a consistent heterogeneity of the model and evidenced a significant risk of publication bias, so were excluded from the analysis. This exclusion, however, did not influence the overall result, by confirming the increased risk of cardiovascular recurrences for patients with a poor response to clopidogrel treatment (OR 3.58, 95%CI 2.54 to 5.05; p<0.00001). The present updated meta-analysis documents a significant association between residual platelet reactivity under clopidogrel treatment and recurrent cardiovascular events, so suggesting the relevance of ongoing interventional studies aimed at tailoring the antithrombotic therapy in CAD patients.
Keywords: Clopidogrel; antiplatelet therapy; clinical recurrences; meta-analysis